A comparative analysis of radical cystectomy with perioperative chemotherapy, chemoradiation therapy, or systemic therapy in patients with clinically advanced node-positive bladder cancer (cN2/N3) - Garg, Harshit; Bhandari, Mukund; Dursun, Furkan; Liss, Michael A.; Kaushik, Dharam; Svatek, Robert S.; Mansour, Ahmed M. (Frontiers in Oncology, 2024)
Abstract Introduction The management of non-metastatic clinically advanced lymph nodal (cN2/N3) bladder cancer (Stage IIIB) could involve radical cystectomy, chemoradiation, or systemic therapy alone. However, a definitive comparison between these approaches is lacking. This study aims to compare the outcomes of patients undergoing radical cystectomy with pelvic lymph node dissection (RC-PLND), chemoradiation therapy (CRT) or systemic therapy (including immunotherapy) (ST) only in patients with stage IIIB bladder cancer. Materials and methods: A retrospective analysis of the National Cancer Database for patients with stage IIIB urothelial bladder cancer was done from 2004-2019. Patients were classified as Group A: Those who received RC-PLND with perioperative chemotherapy, Group B: Those who received CRT, and Group C: Those who received only ST alone. The primary outcome was overall survival (OS). Inverse probability weighting (IPW)-adjusted Kaplan Meier curves were utilized to compare overall survival (OS) and cox multivariate regression analysis was used to identify predictors for OS. Results Overall, 2,575 patients were identified. They were classified into Group A (n=1,278), Group B (n=317) and Group C (n=980). Compared to Group B, patients in Group A were younger (SMD=19.6%), had lower comorbidities (SMD=18.2%), had higher income (SMD=31.5%), had private insurance (SMD= 26.7%), were treated at academic centres (SMD=29.3%) and had higher percentage of N2 disease (SMD=31.1%). Using IPW-adjusted survival analysis, compared to Group C, the median OS was significantly higher in Group A (20.7 vs 14.2 months, p<0.001) and Group B (19.7 vs 14.2 months, p<0.001) but similar between Group A and Group B (20.9 vs 19.7 months, p=0.74). Both surgery (HR=0.72 (0.65-0.80), p<0.001) and CRT (0.70 (0.59-0.82), p<0.001) appeared to be independent predictors for OS on cox-regression analysis. The major limitations include bias due to retrospective analysis and non-assessment of cancer-specific survival. Conclusion In stage IIIB bladder cancer with advanced lymph nodal disease, both RC and CRT offer equivalent survival benefits and are superior to systemic therapy alone.